(untitled) (Studia Prawnicze / The Legal Studies, 1981)
The article presents the selected problems of the amended in 31.01. 1981, Po¬lish Code of Administrative Procedure. Those problems are considered by the author in comparison with similar procedural institutions in other European so¬cialist countries. The first part of this article describes the conditions and the history of the amended regulation. In author’s opinion the differences in scope of codified and uncodified administrative procedures in compared countries are caused by dif¬ferend legislative techniques employed, by different levels of legal and social de¬velopment and conditions in which the administrative organs are operating. The changes in the Polish procedure, with respect to the time-limit for the decision to be taken by a given organ and complains on the so-called "silence" of the administrative organs, respond with a general tendency of shorting the waiting period for the administrative decision. The Polish legislator has introduced an institution of an administrative settlement (conciliation) — similar institution can be found in Yugoslavian and Czechoslovakian regulations. The fundamental question of the stability of the administrative decision has been regulated accordingly with the postulates of legal writers and solutions, ac¬cepted in other socialist countries; the legislator, in the most favorable manner has solved the contradiction between the postulate of stability of the legal system and the ideological values of the legal administrative decision. Legal rules widening the responsibility of the States Treasury for damages caused by the activities of state administration consist a certain innovation of Polish regulation. The most significant is, however, an introduction, by the amendment, of an administrative court system. In Poland the right to settle an administrative dispute has been allocated with a separate administrative court (the Supreme Administrative Court). The Polish solution differs substantially from constructions accepted in other socialist countries with respect to the legal structures of judicial control over the administrative decisions.